Are there digital tech bubbles in China? - Qin, Meng; Su, Chi-Wei; Qiu, Lianhong; Lobonţ, Oana-Ramona (Technological and Economic Development of Economy, 2024)
This exploration employs the generalized supremum augmented Dickey-Fuller (GSADF) approach to explore whether there are digital tech bubbles in China. The empirical results suggest the existence of multiple digital tech bubbles, which are mostly accompanied by an excessive rise. However, the appearance of digital tech bubbles is curbed since 2016, mainly due to the increasing mature regulations in relevant fields. Besides, bubbles in different digital technologies are similar during the same period, which could be attributed to the close relationships among them. Additionally, we further investigate the factors influencing the explosive behaviours, and find that the Chinese stock market positively affects digital tech bubbles, while economic policy uncertainties and situations negatively influence such explosive behaviors. In the context of the new round of scientific and technological revolution and industrial transformation, these conclusions provide valuable implications to achieve the target of constructing a “Digital China” by becoming moderately cautious about potential bubbles in the digital tech industry.First published online 11 October 2023